Differences in Physical Activity and Academic Performance between Urban and Rural Schoolchildren in Slovenia - Vedrana Sember; Shawnda A. Morrison; Gregor Jurak; Marjeta Kovac; Gregor Starc (Montenegrin Sports Academy, 2018)
In Slovenia, the existing studies of relations between physical activity (PA), academic performance (AP) and urbanization grade have used subjective self-reporting tools for assessing physical activity, which usually led to an underestimation of true PA. We have attempted to overcome this and have investigated the link between PA in rural and urban Slovenian schoolchildren by an objective assessment of PA, using a multi-sensor SenseWear PRO armband. The analysis showed that urban children in Slovenia are more physically active than rural children are and achieve better AP (mathematics grade). Additionally, children who are active between 60 and 120 minutes of MVPA/day have higher AP than their peers who are active less than 60 or more than 120 minutes, whereas the latter groups did not differ in academic performance.